2021
DOI: 10.1159/000521576
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal Injection Is Associated with Increased Posterior Capsule Rupture Risk during Cataract Surgery: A Meta-Analysis

Abstract: Background: Although observational studies have suggested that prior intravitreal therapy may predict posterior capsule rupture (PCR) during cataract surgery, this finding is still controversial. Objective: To summarize current evidence on the association between prior intravitreal injection (IVI) and PCR during cataract surgery. Methods: A systematic literature search was performed up to October 27th, 2021. Pooled odds ratios (ORs) and 95% confidence intervals (CIs) were calculated using random-effects models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0
3

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 43 publications
1
3
0
3
Order By: Relevance
“…8,9,12 There is a much wider range (1.41% to 7%) reported in the literature for PCR in eyes that previously received intravitreal injections. 13 We found a similar PCR rate between the NvAMD and the reference groups (2.90% vs 2.77%). In agreement with other studies, our logistic regression model found a higher likelihood of PCR in eyes receiving ≥10 intravitreal injections before cataract surgery.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…8,9,12 There is a much wider range (1.41% to 7%) reported in the literature for PCR in eyes that previously received intravitreal injections. 13 We found a similar PCR rate between the NvAMD and the reference groups (2.90% vs 2.77%). In agreement with other studies, our logistic regression model found a higher likelihood of PCR in eyes receiving ≥10 intravitreal injections before cataract surgery.…”
Section: Discussionsupporting
confidence: 64%
“…In agreement with other studies, our logistic regression model found a higher likelihood of PCR in eyes receiving ≥10 intravitreal injections before cataract surgery. 13,14 We postulate that repeated intravitreal injections in NvAMD may be associated with lenticular trauma, possibly leading to less integral support of the capsule structure. Another possibility is the inadvertent iatrogenic trauma to the zonular fibers at the time of injection leading to capsular instability at the time of cataract surgery, possibly increasing the risk for PCR.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interessanterweise beschreiben neuere Studien einen höheren Anteil an hinteren Kapselrupturen (HKR) während der Kataraktoperation bei Patienten, die vor- her eineIVOM-Behandlungerhaltenhaben [14][15][16]. Dabei korreliert die Inzidenz an HKR mit der Anzahl an Injektionen, ohne dass eine offensichtliche Schädigung der hinteren Kapsel vorlag.…”
Section: Hintergrundunclassified